WORK STRESS AND TURNOVER INTENTION AMONG RETAIL EMPLOYEES: A SYSTEMATIC LITERATURE REVIEW - Nurul Fadia Haya (Journal Analytica Islamica, 2026)
Employee turnover intention remains one of the major challenges in the retail industry, as it contributes to increased recruitment and training costs, reduced workforce productivity, and disruptions to organizational stability. Previous studies have consistently identified job stress as a significant psychological factor influencing employees' intention to leave their organizations. This study aims to examine and synthesize empirical evidence regarding the relationship between job stress and turnover intention among retail employees through a literature review employing a systematic narrative approach. Relevant literature was retrieved from Google Scholar, ScienceDirect, SpringerLink, and Emerald Insight, covering publications from 2022 to 2026. A total of 15 articles that met the predefined inclusion criteria were analyzed using descriptive analysis, thematic analysis, and narrative synthesis. The findings indicate a consistently positive relationship between job stress and turnover intention. Factors such as excessive workload, emotional labor, abusive customer behavior, job insecurity, and burnout were found to increase employees' intention to leave their organizations. Conversely, job satisfaction, organizational commitment, supportive leadership, job security, and work–life balance emerged as protective factors that mitigate turnover intention. These findings highlight the importance of effective job stress management, coupled with the enhancement of employees' psychological resources, as a strategic approach to improving employee retention within the retail sector.